PENERAPAN METODE FUZZY MAMDANI UNTUK PEMETAAN STUNTING DI KABUPATEN ENDE - Andreas Curtis Hopper Fua; Yampi R Kaesmetan (Jurnal Publikasi Manajemen Informatika, 2025)
Stunting is a chronic growth disorder in children that impacts health, economic productivity, and quality of life. Ende Regency, located in East Nusa Tenggara Province, has recorded a high prevalence of stunting, with cases increasing by 8.2% in 2024. This research involves collecting secondary data and applying the Fuzzy Mamdani method through the stages of fuzzification, fuzzy rule formation, fuzzy inference, and defuzzification. The mapping results are expected to provide a comprehensive overview of stunting distribution and its determinants, serving as a basis for policymakers to design targeted interventions.This study also contributes to the advancement of science and technology (IPTEKS) through the application of the Fuzzy Mamdani method in health mapping and aims to raise public awareness to support stunting prevention efforts. The research aims to apply the Fuzzy Mamdani method in mapping stunting in Ende Regency, identify areas with the highest stunting prevalence, and determine the main factors influencing its distribution, enabling communities to increase awareness and participation in stunting prevention efforts based on accurate information.